Drivers' analysis of trajectories (commercial, logistical, and financial) of China's export performance: A comparative analysis between Eastern and South-Eastern Asian countries - Diana Escandón Barbosa; Jairo Salas-Páramo; Ana Virginia Moreno-Charry (Research in Globalization, 2023)
Purpose: The present research aims to study the driver's analysis trajectories (commercial, logistical, and financial) of China's export Performance, comparing eastern countries (Japan) and south-eastern countries (Singapore, Hong Kong, South Korea, Philippines) between 1975 and 2022. For the research purpose, a growth trajectories model was used. This technique considers commercial, logistical, and financial drivers and their impact on export performance. The world bank database is used for this analysis. It contains information on the specified Asian countries and years. The growing trajectory analysis model is a data analysis technique that allows for identifying variations in the drivers in the time that have characterized the export dynamics of Asian Countries. The results show what drivers have been the ones that have had the most significant influence on countries' export performance.
Keywords: 330; Export performance; Internationalization; The behavioral theory of the firm; Trajectory analysis